Caracterización de flujos vehiculares en intersecciones viales de Bogotá, Colombia (2020)
The design of road intersections represents an important part of a city's public expenditure for new road infrastructure projects. Also, it is a step of the planning and land management processes. The objective of this document is to characterize the vehicle flow of road intersections in Bogotá, according to their turning behavior. Using Volume Vehicle reports available in open databases, 305 intersections distributed throughout the city were randomly selected. From these intersections, information about their identification, disaggregated vehicle flow and their physical and operational characteristics was extracted. As a result, the empirical probability functions were obtained for each type of intersection classified, according to the distribution of their accesses and their typology. Additionally, the heterogeneity of the average behavior of the vehicle flow in the periods of maximum demand in the morning and the afternoon was analyzed. The estimation of the a priori turn flow probabilities of the intersections is not only useful for their design, but it can also be used as an initial parameter of the different balancing algorithms for transport networks.